Pengaruh Gaya Kepemimpinan Demokratis dan Motivasi Terhadap Produktivitas Kerja Karyawan PT. Maxirpo Group Indonesia Surabaya - Cindy Eka Ainur Putri; Iswati Iswati; Anis Fitriyasari; Arief Widijatmoko (Jurnal Strategi Bisnis Teknologi, 2025)
This study wants to find out more about "The Influence of Democratic Leadership Style and Motivation on Employee Work Productivity" in accordance with the main problem raised, namely the relationship between democratic leadership style and the impact of employee motivation in completing tasks at PT. Maxipro Group Indonesia. The background of this research is that there have been many cases that occur in companies caused by ineffective leadership. Leadership style is considered effective if it can involve the ability of a leader to motivate his employees and manage the team in an efficient and productive way. Thus, PT Maxipro Group Indonesia uses a democratic leadership style in running its company, as a company that prioritizes employee opinions in advancing the company. The purpose of this study is to find out: how the role of employees in participating in advancing the company, cooperation between teams in the company, how the relationship between managers and employees, what are the motivations that can be a motivation for employees in the company. The method used in this study is quantitative method.